The southern Sporades: An integrated research attempt apllied to the study of the human ecology of micro insular units - Vernicos, Genevieve; Vernicos, Nicolas (The Greek Review of Social Research, 1981)
The deep changes Greece experienced during the thirty years follow ing the endof the hostilities permit us to hope that neo-Hellenic socie ty is about to become aware of the ecological dimension of any economic and social development. From this moment on, it is necessary to provide ourselves with a global method capable of com bining the observation of social relations with that of relations be tween men and nature. A systemic approach to human ecology allows us to unite the subsystems of nature (basis) and of society (acts) with the help of a third element corresponding to culture (the sub system of regulations). Applied to a survey led in the Southern Sporades, this method has brought to the fore a first series of pro cesses governing the recent evolution of these micro-insular societies. Simply to illustrate the method, are mentioned, among these pro cesses, problems related to the preservation of the local sylva, the historical evolution of the structureof distribution of the island space between human establishments and crops, the process of the adapta tion of a small island’s economy to an exterior market as well as the economic rules directing this adaptation. The management of the area and of its resources, as well as the dependence, a micro-insular community faces in regard to the surrounding world, reveal the in herent fragility of the nature, society and culture of minor islands.